EXPLORING STUDENTS' PERCEPTION OF LISTENING SKILL IN PUBLIC SPEAKING: A PRAGMATIC APPROACH TO CORRECTING CONSTRUCTIVE ERRORS - Dinda Asyfa Lukman; Akhmad Haqiqi Ma’mun (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study investigates the beliefs of the students in the fourth semester of English Education at University Muhammadiyah Prof. Dr. Hamka on the relevance of listening skills in public speaking. Using descriptive qualitative approach, the Likert-scale questionnaires and semi-structured interviews were applied as data-gathering tools to investigate the perception of students, their difficulties and their approaches towards the incorporation of listening as an act in their performance of speaking. The results showed that the students realized that listening is an important and dynamic part of quality communication, which supports audience awareness, speech clarity and confidence. However, many of them continue to struggle to create a balance between the delivery of their content and the immediate reaction of the audience. In the pragmatic approach, students began to recognize false positives in listening and also used reflection-based strategies such as the use of feedback and practicing presentations. An aspect raised in this study is the importance of pedagogical activities that support the development of listening as an active and formative skill that contributes to communicative competence in the area of the spoken word.